Finding the genes to build C4 rice - Wang, P; Vlad, D; Langdale, J (Elsevier, 2016)
Rice, a C3 crop, is a staple food for more than half of the world's population, with most consumers living in developing countries. Engineering C4 photosynthetic traits into rice is increasingly suggested as a way to meet the 50% yield increase that is predicted to be needed by 2050. Advances in genome-wide deep-sequencing, gene discovery and genome editing platforms have brought the possibility of engineering a C3 to C4 conversion closer than ever before. Because C4 plants have evolved independently multiple times from C3 origins, it is probably that key genes and gene regulatory networks that regulate C4 were recruited from C3 ancestors. In the past five years there have been over 20 comparative transcriptomic studies published that aimed to identify these recruited C4 genes and regulatory mechanisms. Here we present an overview of what we have learned so far and preview the efforts still needed to provide a practical blueprint for building C4 rice.